![image](https://tex.z-dn.net/?f=x_n%3Dx_1%2Aq%5E%7Bn-1%7D%5C%5C%0Ax_2%3Dx_1%2Aq%3D-2%5C+%3D%3E%5C+x_1%3D%5Cfrac%7B-2%7D%7Bq%7D%5C%5C%0Ax_4%3Dx_1%2Aq%5E3%3D-6%5C+%3D%3E%5C+x_1%3D%5Cfrac%7B-6%7D%7Bq%5E3%7D%5C%5C%0A%5Cfrac%7B-2%7D%7Bq%7D%3D%5Cfrac%7B-6%7D%7Bq%5E3%7D%5C%5C%0Aq%3D%5Csqrt3%5C%5C%0Ax_7%3Dx_1%2Aq%5E6%3Dx_1%2Aq%2Aq%5E5%3Dx_2%2Aq%5E5%5C%5C%0Ax_7%3D-2%2A%28%5Csqrt3%29%5E5%3D-2%2A9%5Csqrt3%3D-18%5Csqrt3)
\ x_1=\frac{-2}{q}\\
x_4=x_1*q^3=-6\ =>\ x_1=\frac{-6}{q^3}\\
\frac{-2}{q}=\frac{-6}{q^3}\\
q=\sqrt3\\
x_7=x_1*q^6=x_1*q*q^5=x_2*q^5\\
x_7=-2*(\sqrt3)^5=-2*9\sqrt3=-18\sqrt3" alt="x_n=x_1*q^{n-1}\\
x_2=x_1*q=-2\ =>\ x_1=\frac{-2}{q}\\
x_4=x_1*q^3=-6\ =>\ x_1=\frac{-6}{q^3}\\
\frac{-2}{q}=\frac{-6}{q^3}\\
q=\sqrt3\\
x_7=x_1*q^6=x_1*q*q^5=x_2*q^5\\
x_7=-2*(\sqrt3)^5=-2*9\sqrt3=-18\sqrt3" align="absmiddle" class="latex-formula">